Mengukur Tingkat Determinasi Variabel Makroekonomi Terhadap Kinerja Reksadana Syariah Menggunakan Error Correction Model - Yudhistira Ardana; Etty Puji Lestari; Suhartono Suhartono (Universitas Muhammadiyah Surabaya, 2020)
At present, investment is considered important in line with the uncertainty of global economic conditions. The public is required to be creative in financial management. Among them is by investing in Islamic mutual funds. This study aims to analyze the short-term and long-term effects of Bank Indonesia interest rates, exchange rates and inflation on the performance of Islamic mutual funds in Indonesia using the Error Correction Model. The results show that in the short-term and long-term periods simultaneously, all variables (Bank Indonesia interest rates, exchange rates and inflation) significantly influence the performance of Islamic mutual funds in Indonesia. In the short-term period, the exchange rate and inflation partially have a positive and insignificant effect, while Bank Indonesia interest rates have a negative and no significant effect on the performance of Islamic mutual funds. In the long term period, the exchange rate and inflation partially have a positive and significant effect, while Bank Indonesia interest rates have a negative and significant effect on the performance of sharia mutual funds.